2022
DOI: 10.1038/s41467-022-31361-w
|View full text |Cite
|
Sign up to set email alerts
|

Photo-tailored heterocrystalline covalent organic framework membranes for organics separation

Abstract: Organics separation for purifying and recycling environment-detrimental solvents is essential to sustainable chemical industries. Covalent organic framework (COF) membranes hold great promise in affording precise and fast organics separation. Nonetheless, how to well coordinate facile processing—high crystalline structure—high separation performance remains a critical issue and a grand challenge. Herein, we propose a concept of heterocrystalline membrane which comprises high-crystalline regions and low-crystal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 40 publications
(33 reference statements)
0
21
0
Order By: Relevance
“…Overcoming the limitations of polymeric membranes, separation membranes constructed by two-dimensional (2D) materials have exhibited unique attributes in precise molecular sieving owing to their unique nacre-like structures and ultrafast mass transport. As typical 2D materials, graphene-based membranes consisting of an atom-thick 2D carbon lattice and oxygen functional groups have emerged as candidates for nanofiltration due to unimpeded water permeation, excellent chemical resistance, easy solution processability, and mechanical strength. Functionalized 2D membranes with advanced performances have achieved great progress and shown potential in many applications. Recently, several pioneering works have focused on developing polymer-decorated 2D membranes to modulate the permeation of water and ion molecules by external stimuli such as pH, gas, light, and temperature. However, most previous attempts were based on modulating the molecular configuration or surface hydrophilicity of graphene-based membranes. , Moreover, similar to the polymer-based membranes, the response of polymer-decorated graphene-based membranes often takes tens of minutes (>30 min) to respond to external factors and restore to the original state, owing to the diffusion of signal chemicals and the relaxation of polymer chains. Therefore, fast, reversible, and remote control of graphene-based membranes are highly desired in practical applications. Zhou et al developed a fast-response graphene oxide (GO) based membrane to electrically control water permeation by introducing conductive filaments via electrical breakdown and ionizing the water cluster within the 2D capillary . Meanwhile, Li et al demonstrated a nanoporous graphene-based membrane to accelerate ion diffusion by modulating the interfacial electrical double layer under an external electrostatic field .…”
mentioning
confidence: 99%
“…Overcoming the limitations of polymeric membranes, separation membranes constructed by two-dimensional (2D) materials have exhibited unique attributes in precise molecular sieving owing to their unique nacre-like structures and ultrafast mass transport. As typical 2D materials, graphene-based membranes consisting of an atom-thick 2D carbon lattice and oxygen functional groups have emerged as candidates for nanofiltration due to unimpeded water permeation, excellent chemical resistance, easy solution processability, and mechanical strength. Functionalized 2D membranes with advanced performances have achieved great progress and shown potential in many applications. Recently, several pioneering works have focused on developing polymer-decorated 2D membranes to modulate the permeation of water and ion molecules by external stimuli such as pH, gas, light, and temperature. However, most previous attempts were based on modulating the molecular configuration or surface hydrophilicity of graphene-based membranes. , Moreover, similar to the polymer-based membranes, the response of polymer-decorated graphene-based membranes often takes tens of minutes (>30 min) to respond to external factors and restore to the original state, owing to the diffusion of signal chemicals and the relaxation of polymer chains. Therefore, fast, reversible, and remote control of graphene-based membranes are highly desired in practical applications. Zhou et al developed a fast-response graphene oxide (GO) based membrane to electrically control water permeation by introducing conductive filaments via electrical breakdown and ionizing the water cluster within the 2D capillary . Meanwhile, Li et al demonstrated a nanoporous graphene-based membrane to accelerate ion diffusion by modulating the interfacial electrical double layer under an external electrostatic field .…”
mentioning
confidence: 99%
“…Through pores in COFs possess the superiority of uniform but tunable aperture sizes typically lower than 10 nm and appreciable structural robustness. These features make COFs a highly promising platform for catalysis, separation, control release, and many other applications where the mass transfer in the confined pores plays a significant role in determining the performances. Specifically, COF-based membranes are expected to show nanofiltration performances with high separation precision, which are thought to be superior to conventional membranes made by amorphous polymers. However, COF crystallites tend to grow randomly, forming a polycrystalline structure with the pore channels anisotropically oriented in all directions (Figure a). In this regard, anisotropic orientation compromises the well-defined structures of the through pores and increases the grain boundaries that lead to defect-like intercrystalline gaps, impairing the separation precision.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the atomic thickness of two-dimensional (2D) nanosheets, such as graphene oxide, MXene, MoS 2 , ZIF, MOF, and COF nanosheets, holds great potential for high flux and selectivity in the membrane separation process. As a good compromise choice, a new emerging class of sieving membranes was fabricated by restacking the exfoliated nanosheets after gathering the cost of monolayer 2D nanosheet production and technically challenging the precise pore size on 2D nanosheets. , The restacked exfoliated 2D nanosheets create interconnected nanofluidic channels for ionic and molecular transport, showing potential benefits in pharmaceutical and petrochemical industries. , Unfortunately, the representative GO and MXene nanosheet-based membranes made from solely exfoliated nanosheets tend to lose the integrity of the physical structure or even damage the chemical constituents in an aqueous environment. Even though some pioneering work has been reported to stabilize the 2D nanosheet membrane, the inevitable sacrifice of separation performance weakens the potential practical value and causes additional cost. , Furthermore, the several micron lateral size of the 2D nanosheets and the relatively high viscosity and size of the organic solvents contribute to decreasing permeance of the solvents through the restacked membranes. Hence, 2D nanosheet-based membranes with high chemical and physical stability and flux remain a challenge for future industrial applications …”
Section: Introductionmentioning
confidence: 99%